2017
DOI: 10.1542/peds.2017-2289
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Sexual Dating Violence and Nonmedical Use of Prescription Drugs

Abstract: BACKGROUND:Little information is available on the associations between nonmedical use of prescription drugs (NMUPD) and dating violence victimization (DVV) among high school students and how associations vary by sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…In line with our study, Brady, Tschann, Pasch, Flores and Ozer (2008) found that adolescents who had experienced sexual violence at age 15 were more likely to use tobacco at age 19, and those who had multiple sexual partners were more likely to use marijuana at age 19 (Brady et al, 2008). Additionally, studying the association between non-medical use of the prescription drug (NMUPD) and sexual violence among adolescents, Clayton et al (2017) reported that male victims of sexual violence were 1.61 times more likely to use NMUPD than those who did not experience sexual violence [AOR: 1.61; 95%CI: 1.21-2.12]. However, the association was not significant among female victims of sexual violence (Clayton, Lowry, Basile, Demissie, & Bohm, 2017).…”
Section: Sexual Violence and Substance Usesupporting
confidence: 79%
See 1 more Smart Citation
“…In line with our study, Brady, Tschann, Pasch, Flores and Ozer (2008) found that adolescents who had experienced sexual violence at age 15 were more likely to use tobacco at age 19, and those who had multiple sexual partners were more likely to use marijuana at age 19 (Brady et al, 2008). Additionally, studying the association between non-medical use of the prescription drug (NMUPD) and sexual violence among adolescents, Clayton et al (2017) reported that male victims of sexual violence were 1.61 times more likely to use NMUPD than those who did not experience sexual violence [AOR: 1.61; 95%CI: 1.21-2.12]. However, the association was not significant among female victims of sexual violence (Clayton, Lowry, Basile, Demissie, & Bohm, 2017).…”
Section: Sexual Violence and Substance Usesupporting
confidence: 79%
“…Additionally, studying the association between non-medical use of the prescription drug (NMUPD) and sexual violence among adolescents, Clayton et al (2017) reported that male victims of sexual violence were 1.61 times more likely to use NMUPD than those who did not experience sexual violence [AOR: 1.61; 95%CI: 1.21-2.12]. However, the association was not significant among female victims of sexual violence (Clayton, Lowry, Basile, Demissie, & Bohm, 2017).…”
Section: Sexual Violence and Substance Usementioning
confidence: 99%
“…NMUPD has increased steadily among young people in the last decade (usually linked to self-treatment, experimentation, and readily accessibility), and the consequent incidence of unintentional overdoses has reached epidemic levels [11,12,13]. In addition, NMUPD is a risk factor for suicide [14,15], negative sexual behavior [16,17], and poor social functioning [18].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from cross‐sectional studies have found that sexual assault history and prescription opioid misuse are associated among adolescent girls . Specifically, among a national sample of adolescents, results indicated that girls with a sexual assault history were more than four times more likely to use drugs which included non‐medical use of prescription medications than those without a sexual assault history .…”
mentioning
confidence: 99%